Autonomous Regulator of Tremor (ART) (2023)
Essential tremor (ET) stands as one of the most prevalent neurological disorders globally, affecting over 400 million individuals. Typically impacting those aged 20 to 60, ET significantly diminishes the quality of life, particularly in fine motor skills control, notably within the upper limbs. This impairment hinders everyday tasks like writing, drawing, and eating, often leading to complications and an increased susceptibility to Parkinson's disease. Traditional approaches for tremor reduction involve invasive measures such as medication, deep brain stimulation, and focused ultrasound via magnetic resonance, alongside emerging electrotherapy treatments. However, these solutions tend to be either invasive or expensive, with even the most cost-effective innovations facing availability challenges, especially in countries like Colombia. Recognizing the need for accessible, low-cost solutions, we introduce ART: Autonomous Regulator of Tremor.